The Study of Added Value Analysis of Coffee Processing in Indonesia - Ni Luh Made Indah Murdyani Dewi; I Putu Iwan Pramana Putra; I Kade Astama (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
Coffee is one of the largest foreign exchange earning commodities for Indonesia. In 2021 the area of coffee plantations in Indonesia is 1,258,800 ha. This area is wider than in 2019 and 2020. Meanwhile, the total coffee production in 2021 is 774.60 tons. The five provinces in Indonesia that have the most coffee production are the provinces of South Sumatra, Lampung, North Sumatra, Aceh and Bengkulu. The highest production can encourage processing activities. Coffee processing is the process of changing form from primary form to secondary form. Coffee processing is also expected to provide added value for businesses that carry out processing activities. Value added is the added value of a commodity due to processing, transportation or storage in a production process. The various types of coffee can affect the added value for businesses in several regions in Indonesia. Therefore, it is important to do a comparative analysis of the added value of coffee processing in Indonesia to inform how much the level of added value exists in several regions in Indonesia. The data used in this study is secondary data derived from previous studies by collecting several journals used as a reference in carrying out the study. The literature study method using data collection tools to reveal various theories that are relevant to the problem being faced or researched as material for discussing the results of the study taken from various books that are considered relevant to the content of the study. Of the five value-added studies that have been reviewed, the highest value-added ratio is in the Luwak Coffee Agroindustry, Balik Bukit District, West Lampung Regency and Pulau Panggung District, Tanggamus Regency, Lampung Province, from the primary form of coffee cherries to the secondary form of civet coffee beans, namely 72.97%. This means that only Luwak Coffee Agroindustry, Balik Bukit District, West Lampung Regency and Pulau Panggung District, Tanggamus Regency, Lampung Province, has high added value because it has an added value ratio of 40%.